Service Systems Implementation - Demirkan, Haluk; Spohrer, James C.; Krishna, Vikas (Service Science: Research and Innovations in the Service Economy,1865-4924, 2011)
Service Systems Implementation provides the latest applications and practices aimed at improving the key performance indicators of service systems, especially those related to service quality, service productivity, regulatory compliance, and sustainable service innovation. The book presents action-oriented, application-oriented, design science-oriented (artifacts building: constructs, models, methods and instantiations) and case study-oriented research with actionable results by illustrating techniques that can be employed in large scale, real world examples. The case studies will help visualize service systems along the four key dimensions of people, information, technology and value propositions which can help enable better integration between them towards higher value propositions. The chapters, written by leading experts in the field, examine a wide range of substantive issues and implementations related to service science in various industries. These contributions also showcase the application of an array of research methods, including surveys, experiments, design science, case studies and frameworks, providing the reader with insights and guidelines to assist in building their own service systems, and thus, moving toward a more favorable service customer and provider experience. Service Systems Implementation, along with its companion text, The Science of Service Systems, is designed to present multidisciplinary and multisectoral perspectives on the nature of service systems, on research and practice in service, and on the future directions to advance service science. These two volumes compose a collection of articles from those involved in the emerging area known as service science.